ANALISIS PENGARUH KUALITAS JARINGAN, KUALITAS LAYANAN, KUALITAS INFORMASI, KEAMANAN DAN PRIVASI PADA PENYEDIA LAYANAN INTERNET TERHADAP KEPUASAN PELANGGAN DAN DAMPAK PADA NIAT PEMBELIAN ULANG - Ilham, Yusuf; Bayu Dirgantara, I Made (Faculty of Economics and Business Diponegoro University, 2020)
The initial emergence of the internet in Indonesia in the 1990s was known as Paguyuban Network (Network community). It is known as the Paguyuban Network because at this time its users had intimate relationship, high togetherness and great mutual cooperation. The users did these actions in order to carry out trade and communication among students who were abroad. Ipteknek had an important role in Indonesia as Ipteknek was the first internet network service provider to have a new revolution, then encouragen the emergence of other ISPs in Indonesia. Various internet service providers or ISPs in Indonesia include Biznet Home Internet, First Media, Indihome, Indosat Oorodeoo GIG, MNC Play Media, MyRepublic, Oxygen.Id home. This study analyzes the influence of large networks quality, service quality, information quality, security and privacy of internet service providers on the customer satisfaction and repurchase-intention. The populations used in this study were customers who have used internet services in Semarang. The sample used was 215 respondents. The method of sample collection uses a purposive sampling technique. Data collection methods used were questionnaires. This research uses Structural Equation Modeling (SEM) analysis with AMOS 24.0 analysis tools. The results of this study indicate service quality, information quality, security and privacy are positive and significant for customer satisfaction. Network quality is not positive for customer satisfaction. Furthermore, customer satisfaction has positive and significant influence to repurchase intention.